Pengembangan Media Buku Cerita Bergambar Untuk Meningkatkan Pemahaman Anak Tentang Mitigasi Bencana - Melina Yuli Kartika; Vit Ardhyantama; Urip Tisngati (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2023)
This research aims to develop a picture storybook to increase childrens’ understanding about earthquake and tsunami disaster mitigation. This type of research is Research and Development (R&D) with the ADDIE development model which consists of five stages, namely, analysis, design, development, implementation, and evaluation. The data collection techniques used were observation, tests, questionnaires, and documentation. The data analysis technique used is the analysis of the level of validity of the product and the data analysis of the test results with paired sample t tests. The results showed that: (1) the earthquake and tsunami disaster mitigation picture storybook media has been developed using the ADDIE model, (2) the picture storybook media is declared